Mucosal Exosome Proteomics of Hybrid Grouper Epinephelus fuscoguttatus♀ × E. lanceolatus♂ Infected by Pseudomonas plecoglossicida - Dong Yang; Xiaowan Ma; Shengping Zhong; Jiasen Guo; Dewei Cheng; Xuyang Chen; Teng Huang; Lixing Huang; Ying Qiao; Theerakamol Pengsakul (Animals, 2024)
Pseudomonas plecoglossicida infection, which causes visceral white spot disease, is a significant and economically devastating disease in aquaculture. In this study, we investigated the impact of bacterial infection on the protein composition of exosomes derived from the surface mucus of the hybrid grouper Epinephelus fuscoguttatus♀ × E. lanceolatus♂. Two hundred healthy fish were randomly separated into challenge and control groups. Fish from the challenge group received 103 CFU/g of the bacterial pathogen P. plecoglossicida via intraperitoneal injection, while sterile PBS was used as a negative control. After injection, the mucus was collected and the exosomes were extracted for proteomic analysis. The results of proteomic analysis revealed that P. plecoglossicida infection significantly increased the levels of innate immune proteins, including lysosomal and peroxisomal proteins, within the exosomes. Furthermore, the CAD protein was found to play a pivotal role in the protein interaction networks involved in the response to P. plecoglossicida infection. Intriguingly, we also observed a significant increase in the levels of metal-binding proteins within the exosomes, providing important evidence of nutritional immunity on the surfaces of the fish hosts. Notably, several proteins, such as plasma kallikrein, Annexin A5, eukaryotic translation initiation factor 3 subunit M, and S-methyl-5-thioadenosine phosphorylase, exhibited a remarkable increase in abundance in exosomes after infection. These proteins show promising potential as noninvasive biomarkers for the diagnosis of visceral white spot disease. The study contributes to the understanding of the host response to P. plecoglossicida infection and may aid policymakers in implementing appropriate intervention measures for effective risk management of this devastating disease.